Combined Effects of Magnetic Field and Slip Parameter on Hydromagnetic Flow Through Porous Media With Different Slip Velocities at Both the Porous Interface - Ramakrishnan, K. (Journal of Informatics and Mathematical Sciences, 2018)
Effects of magnetic field and slip parameter on hydromagnetic flow through a uniform channel covered by porous media with different slip velocities at both the porous interface have been investigated. In the direction perpendicular to the motion of the fluid, a uniform magnetic field is applied. The analytical solution for the equations governing to the problem is obtained by using the Beavers-Joseph slip condition. Slip velocities at both the porous interface are assumed to be different. The flow characteristics such as axial velocity, slip velocity and the shear stress are calculated for different values of Hartmann number, porous parameter and slip parameter. It is observed that due to slip velocity variation in both the upper and lower walls, the distribution of flow pattern have altered.